2011
DOI: 10.1080/17521882.2011.596484
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of executive coaching research: a decade of progress and what's to come

Abstract: Copyright and moral rights to this work are retained by the author and/or other copyright owners unless otherwise stated. The work is supplied on the understanding that any use for commercial gain is strictly forbidden. A copy may be downloaded for personal, non-commercial, research or study without prior permission and without charge.Works, including theses and research projects, may not be reproduced in any format or medium, or extensive quotations taken from them, or their content changed in any way, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 60 publications
4
162
0
3
Order By: Relevance
“…Of these 111 papers 15 were published prior to 2000, with the remaining 96 published since 2004, supporting claims made about an upward trajectory in this area by Ely et al (2010). Thirty five articles were published in 2012 to 2015 further demonstrating that the field of coaching research is developing and that considerably more evidence is now available for consideration than previous narrative reviews such as those provided by Passmore and Fillery-Travis (2011).…”
Section: What Gaps Exist In Research Into Business Coaching?mentioning
confidence: 87%
See 2 more Smart Citations
“…Of these 111 papers 15 were published prior to 2000, with the remaining 96 published since 2004, supporting claims made about an upward trajectory in this area by Ely et al (2010). Thirty five articles were published in 2012 to 2015 further demonstrating that the field of coaching research is developing and that considerably more evidence is now available for consideration than previous narrative reviews such as those provided by Passmore and Fillery-Travis (2011).…”
Section: What Gaps Exist In Research Into Business Coaching?mentioning
confidence: 87%
“…While a variety of scales and measures were used to evaluate the coaching almost all relied upon coachees' and/or coaches' selfreported subjective evaluations of effectiveness. The limitations of using only subjective participant evaluations to assess the success of coaching have been discussed in detail elsewhere (Ely et al, 2010;Passmore & Fillery-Travis, 2011;Passmore & Gibbes, 2007) and include issues such as rating the coach instead of the effectiveness of the coaching process and everything it involves, participants that are going through the coaching process at the time they evaluate it are more likely to rate different aspects more highly compared to those that have time to reflect. Thus, it is not possible from this set of studies to make very strong claims about the effectiveness of coaching in general or its effectiveness compared to other training opportunities.…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the approach chosen here is preferable to using a parametric test incorrectly. Second, the sample size is small compared to, for example, the one hundred plus participants that has been proposed as a standard elsewhere (Passmore & Fillery-Travis, 2011). However, the sample size has sufficient statistical power to detect a large effect which is, after all, the size of effect of most practical value (Friston, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This idea is based on the results of selfregulated learning (Glen, 2010). Passmore & Fillery-Travis (2011) tried to evaluate the effectiveness of this coaching. De Meuse, Dai & Lee (2009) found that coaching led to improvement of skills and task performance.…”
Section: Recent Studies: Coaching and Academic Achievementsmentioning
confidence: 99%